Up and running with AutoCAD 2012 : 2D drawing and modeling - Gindis, Elliot (Waltham, MA : Academic Press, 2012)
'Throughout the book, the following methods are used to present material: - Explain the new concept or command and why it is important. - Cover the command step by step (if needed), with your input and AutoCAD responses shown so you can follow and learn them. - Give you a chance to apply just-learned knowledge to a real-life exercise, drawing, or model. - Test yourself with end-of-chapter quizzes and drawing exercises that ask questions about the essential knowledge'--
Includes index.
Keywords: AutoCAD; Computer graphics; Computer-aided design